Carta dental como medio de identificación (2018)
This investigation, through factual assumptions exemplified through a case, aims to raise awareness of the importance of dentistry, within the forensic sciences in the process of selfidentification of corpses, and that stands as a highly relevant alternative in the administration of justice. In the case of Colombia, the methods used for the identification of cadavers have beenfingerprinting and identification by DNA; second, the dental chart and therefore, the forensic dentist, an expert of vital importance in the interdisciplinary team whose common objective is to achieve full identification. Thus, the dental chart is constituted as a fundamental element to achieve the development ofthe object of the problem proposed in this essay; thus, the survey, the archive, the publicity and the implementation for the application of the scientific method, must be matched through the execution of technical tasks and procedures that will be briefly illustrated in the development of this work. Along with the scientific method that should be coined to this procedure, the odontolegal clinical history is based, together with the antemortem and postmortem dental charts; which should be available when the judicial authority requires them; however, the implementation of such procedures in the country is not carried out, thus generating an additional problem for the Medical Examiner and full identification